Reputation model for b2c e-commerce:a trust flow based on social networks - Che Hussin, Ab. Razak (2011)
Trust and reputation systems enable customers to reliably assess the quality of services and reliability of entities. The aim of reputation system is to let parties rate each other and to help in deciding whether or not to transact with a given party in online environment. In current reputation systems, users have to trust unreliable information sources and anonymous people. There is a need to improve current reputation systems by allowing users to make decision in buying online based on reliable information sources. Therefore this paper proposes a trust flow through sharing of knowledge and experience in reputation systems by utilizing social networks. This can assist users to access trustworthy information sources by knowing the experience and feedback of their friends in the social networks. This approach will improve the motivation of users for buying online and make the experience more enjoyable.